Elution of rifampin and vancomycin from a weight-bearing silorane-based bone cement. Issue 4 (1st April 2021) - Funk, Grahmm August; Menuey, Elizabeth M.; Ensminger, William P.; Kilway, Kathleen V.; McIff, Terence E.
Abstract : Aims: Poly(methyl methacrylate) (PMMA)-based bone cements are the industry standard in orthopaedics. PMMA cement has inherent disadvantages, which has led to the development and evaluation of a novel silorane-based biomaterial (SBB) for use as an orthopaedic cement. In this study we test both elution and mechanical properties of both PMMA and SBB, with and without antibiotic loading. Methods: For each cement (PMMA or SBB), three formulations were prepared (rifampin-added, vancomycin-added, and control) and made into pellets (6 mm × 12 mm) for testing. Antibiotic elution into phosphate-buffered saline was measured over 14 days. Compressive strength and modulus of all cement pellets were tested over 14 days. Results: The SBB cement was able to deliver rifampin over 14 days, while PMMA was unable to do so. SBB released more vancomycin overall than did PMMA. The mechanical properties of PMMA were significantly reduced upon rifampin incorporation, while there was no effect to the SBB cement. Vancomycin incorporation had no effect on the strength of either cement. Conclusion: SBB was found to be superior in terms of rifampin and vancomycin elution. Additionally, the incorporation of these antibiotics into SBB did not reduce the strength of the resultant SBB cement composite whereas rifampin substantially attenuates the strength of PMMA. Thus, SBB emerges as a potential weight-bearing alternative to PMMA for the local delivery of antibiotics. Cite this article: Bone Joint Res  2021;10(4):277–284.